Methodological Challenges in Studying Testosterone Therapies for Hypoactive Sexual Desire Disorder in Women. Issue 4 (13th February 2020) - Rowen, Tami S.; Davis, Susan R.; Parish, Sharon; Simon, James; Vignozzi, Linda
Abstract: Introduction: Testosterone has been studied for its benefits on sexual health for decades. The research regarding testosterone in women has produced evidence that this is a potential treatment for women suffering from female sexual dysfunction. There are several limitations of the testosterone trials that can affect their interpretation and challenges posed by some regulatory agencies that have prevented approval of any testosterone treatment for women in several countries. Aim: To summarize the challenges of testosterone trials in terms of study populations, patient-reported outcomes, validated instruments in research, confounders, and regulatory barriers. Methods: A thorough review of published data on testosterone for the treatment of women's sexual health problems was undertaken. A detailed evaluation of the limitations of these trials was conducted and incorporated with the published evidence on the regulatory processes involved in moving testosterone from clinical research to drug approval. Main Outcome Measure: Main outcome measures are assessment of clinical trial populations, survey tools, confounders, and regulatory barriers. Results: There is some heterogeneity of study populations included in testosterone trials in women. Similarly, there have been differences in instruments used to assess patient-reported outcomes and often minimal control for potential confounders. The regulatory agency had posed a challenge to approve any testosterone treatment for women based on unproven concerns and a lack of regulatory guidance for drug developers. Clinical Implications: There is strong evidence that shows testosterone is effective for treating sexual health concerns in the women included in clinical trials. Strength & Limitations: Strengths include thorough review of published literature and trial design for sexual health concerns. Limitations include being restricted to English Language publications and not having access to unpublished clinical trial data. Conclusions: Testosterone trials in women have been limited by homogeneity in the study populations and outcomes measured. Drug development has been hampered by inconsistent regulatory barriers.